Validating Response of AC Microgrid to Line-to-Line Short Circuit in Islanded Mode Using Dynamic Analysis - , Maruf A. Aminu (Archives of Current Research International, 2019)
This paper is presented in an attempt to validate the dynamic response of a microgrid to line-to-line short circuit. The microgrid components include two identical Wind Turbine Generators (WTGs) tied to a 100MVA, 13.8kV utility via a Point of Common Coupling (PCC). The utility-microgrid testbed is modeled in SIMPOWERSystems® using two Doubly-Fed Induction Generators (DFIGs) in the microgrid side. While in islanded operating mode, line-to-line short circuit fault is applied at 6.0s and withdrawn at 8.0s, obtaining a 50.0s dynamic response of the system for different fault locations, under voltage and reactive power control regimes of the wind turbine controller. For measurement purpose, the absolute value of the stator complex voltage is transformed to reference frame. Bidirectional power flow between the two feeders is established in the study. The study also confirms that the microgrid composed of DFIGs offer reactive power management capability, particularly by presenting superior performance when stressed under Q control regime than under V control regime. Finally, the response of the testbed to line-to-line short circuit has been validated and shown to be consistent with established short circuit theory.